MANUAL COLON-ANAL OR MECHANICAL COLORECTAL ANASTOMOSIS? COMPARATIVE ANALYSIS OF LAPAROSCOPIC LOW RESECTIONS OF THE RECTUM - I. L. Chernikovsky (Сибирский онкологический журнал)
The purpose of the study was to compare immediate surgical outcomes of low anterior resections (LAR) and intersphincteric resections (ISR) of the rectum. Materials and methods. Treatment outcomes of 42 patients operated on between March, 2014 and January, 2015 were presented. Group I consisted of 24 patients who underwent laparoscopic ultra-low anterior resection (uLAR) for rectal cancer. Group II comprised 18 patients who underwent laparoscopic ISR. Results. No significant differences in the median length of surgery and blood loss between two groups were observed. Circular and distal resection margins were negative in all cases. In 18 (75 %) patients of Group I and in 14 (77.7 %) patients of Group II, total mesorectumectomy(TME) was assessed as grade 3 (p=0.83). The frequency of postoperative complications in uLAR-treated group was 20.8 %, not requiring a secondary revision procedure, and 27.8 % in ISR-treated group, requiring repeated surgery. The mean value of the fecal incontinence according to the Wechsler scale in a month after surgery was significantly higher in group II than in Group I patients (9.3 versus 6.2, р=0.01). The average treatment cost for uLAR was higher by 45,000 rubles than that for ISR. Conclusion. Both surgical procedures were matched by the duration of operation, amount of blood loss and the quality of mesorectumectomy. The complication rate was not significantly different between two groups, however, 16.8 % of Group II patients required relaparotomy, likely due to the mastering of the ISR technique. Ultra-low anterior resections of the rectum are functionally preferred. When performing ISR, the technique of reservoir colo-anal anastomosis with preservation of the portion of the internal sphincter provides functional results comparable with those obtained using LAR.